Immunological Features of the Non-Structural Proteins of Porcine Reproductive and Respiratory Syndrome Virus - Rascón-Castelo, Edgar (Viruses, 2015)
Porcine reproductive and respiratory syndrome virus (PRRSV) is currently one of the most important viruses affecting the swine industry worldwide. Despite the large number of papers published each year, the participation of non-structural proteins (nsps) in the immune response is not completely clear. nsps have been involved in the host innate immune response, specifically, nsp1α/β, nsp2, nsp4 and nsp11 have been associated with the immunomodulation capability of the virus. To date, only participation by nsp1, nsp2, nsp4 and nsp7 in the humoral immune response has been reported, with the role of other nsps being overlooked. Furthermore, nsp1, nsp2, nsp5, nsp7 nsp9, nsp10, nsp11 have been implicated in the induction of IFN-γ and probably in the development of the cell-mediated immune response. This review discusses recent reports involving the participation of nsps in the modulation of the innate immune response and their role in the induction of both the humoral and cellular immune responses.